2020
DOI: 10.1042/bsr20192132
|View full text |Cite
|
Sign up to set email alerts
|

MiR-124-3p helps to protect against acute respiratory distress syndrome by targeting p65

Abstract: Background: Acute respiratory distress syndrome (ARDS) is a severe form of acute lung injury that has a high mortality rate and leads to substantial healthcare costs. MicroRNA-124-3p (miR-124-3p) helps to suppress inflammation during a pulmonary injury. However, its mechanism of action is largely unknown, and its role in ARDS remains to be determined. Methods: Mice and NR8383 cells were exposed to lipopolysaccharides (LPS) to induce ARDS, and their miR-124-3p levels were determined. After a miRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…A mice model showed downregulation in miR-124-3p expression in ARDS. Treatment with miR-124-3p agomir attenuated the pulmonary injury and the levels of pro-inflammatory cytokines IL-6 and TNF-α by directly targeting p65, thus showing promise in in-vitro management of pulmonary injury ( Liang et al, 2020 , p. 65).…”
Section: Discussionmentioning
confidence: 99%
“…A mice model showed downregulation in miR-124-3p expression in ARDS. Treatment with miR-124-3p agomir attenuated the pulmonary injury and the levels of pro-inflammatory cytokines IL-6 and TNF-α by directly targeting p65, thus showing promise in in-vitro management of pulmonary injury ( Liang et al, 2020 , p. 65).…”
Section: Discussionmentioning
confidence: 99%
“…There have also been reports of miR-124 acting to attenuate M1 macrophages as a universal regulator of macrophage into the M2 subtype by decreasing NFκB activity in various subsets of monocytic cells and tissue-resident macrophages including lung macrophages ( 65 , 66 ). The dysregulation of miR-142-5p and miR-130a-3p was characterised as an important factor governing the polarization of macrophages with higher levels of M2-like phenotypic markers and was associated with airway remodelling in ovalbumin-sensitized mice ( 67 ).…”
Section: Microrna-based Regulation Of Macrophage Polarization In Immune Response Inflammation and Fibrosismentioning
confidence: 99%
“…Moreover, hsa-miR-124-3p was found to be downregulated in JEV-infected human neural stem cells [61]. The miR-124-3p agomir reduced pro-inflammatory cytokines IL-6 and TNF-α levels and thus was able to protect against pulmonary injury [62]. It has been shown that SARS-CoV-2 hijacks Ddx58 which is involved in miRNA biogenesis and mRNA splicing to help its replication.…”
Section: Discussionmentioning
confidence: 99%